A brief account of Julius Planer's life and research - Bilyy, R.; Lutsyk, A. (Condensed Matter Physics, 2010)
A brief account of the life and research activities of Julius Planer is presented. Professor Planer is a scientist who lived one and half century ago. However, his studies, in particular, during the years when he headed Department of Anatomy at Universit ¨ at in Lemberg, nowadays known as the Ivan Franko National University of Lviv in Ukraine, were essential to a modern understanding of liquid crystals. While working at Lviv University, Planer also made several landmark contributions to biomedical science.